1976
DOI: 10.1172/jci108249
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic mineralocorticoid agonist activity of some nonsteroidal anti-inflammatory drugs. A postulated mechanism for sodium retention.

Abstract: A B S T R A C T Because some nonsteroidal anti-inflammatory drugs (NSAID) induce salt and water retention and exhibit other steroid-like actions, studies were performed to ascertain whether these drugs possess intrinsic mineralocorticoid agonist activity. In vitro competitive binding assays utilizing tissue from adrenalectomized rats demonstrated that some NSAID can displace [3H]-aldosterone from renal cytoplasmic mineralocorticoid receptors. Displacement potency for these sites was in the sequence: aldosteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Indomethacin significantly de creased mean U p^V both during control (0.51 + 0.09 pmol/min; p<0.025)and furo semide administration (0.56 + 0.13 pmol/ min; p<0.025). Previous studies have suggested that indomethacin may have intrinsic sodium-re taining activity by competing with aldoste rone for renal 'mineralocorticoid receptors' [26]. The present results, both with potas sium retention and with marked chloride retention following indomethacin treat ment, would seem to exclude such an intrin sic activity of indomethacin as the mecha nism of the observed salt retention.…”
Section: Urinary Pge2 Excretionsupporting
confidence: 60%
“…Indomethacin significantly de creased mean U p^V both during control (0.51 + 0.09 pmol/min; p<0.025)and furo semide administration (0.56 + 0.13 pmol/ min; p<0.025). Previous studies have suggested that indomethacin may have intrinsic sodium-re taining activity by competing with aldoste rone for renal 'mineralocorticoid receptors' [26]. The present results, both with potas sium retention and with marked chloride retention following indomethacin treat ment, would seem to exclude such an intrin sic activity of indomethacin as the mecha nism of the observed salt retention.…”
Section: Urinary Pge2 Excretionsupporting
confidence: 60%
“…Indeed, identification of the molecular mechanisms underlying the effects of mifepristone on metabolic functions remains to be resolved. We tested several other pharmacological agents chemically or pharmacologically related to mifepristone: GR antagonists, pregnenolone and DHEA; synthetic progestin causing abortion, levonorgestrel; MR antagonist, spironolactone [8,3134]. None of these drugs swere capable of promoting adiponectin secretion ( Hashimoto et al unpublished observation ).…”
Section: Discussionmentioning
confidence: 99%
“…Their data, however, did not entirely support this view (Lees and Michell 1979) and they subsequently confirmed that plasma volume was reduced, even to a degree associated with shock, as a result of intestinal protein loss (Snow et a1 1980). Salt and water retention is a widely acknowledged effect of phenylbutazone, which has inherent aldosterone-like properties and also, through interference with renal prostaglandin synthesis, potentiates the effect of antidiuretic hormone (Feldman and Couropmitree 1976;Dunn and Hood 1977;Hall, Hensey, O'Neill and Sheehan 1978). It has also been shown to interfere with the renin/angiotensin system in horses (Purohit et a1 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported causes of hypomagnesaemia (Parfitt and Kleerekoper 1980) malabsorption seems a possibility in view of the likelihood of enteric protein loss. Although hypomagnesaemia is not a documented side effect of phenylbutazone, it is a recognised consequence of hyperaldosteronism and the drug does bind to the receptor sites for this hormone (Feldman and Couropmitree 1976).…”
Section: Discussionmentioning
confidence: 99%